2021
DOI: 10.1016/j.acra.2021.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Test Accuracy of Deep Learning Detection of COVID-19: A Systematic Review and Meta-Analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 47 publications
0
4
1
Order By: Relevance
“…Therefore, the impact of these 4 aspects on the specificity of DL prediction models needs to be further investigated. In DL model networks, Komolafe et al [ 53 ] found a difference between ResNet and other network models in detecting COVID-19, whereas our study found no significant difference in sensitivity or specificity between ResNet and other network architectures in diagnosing and predicting the severity of COVID-19 ( Table 2 ). This result suggests that, unlike in disease detection, changing the network architecture alone may have little significant impact on DL performance and that factors such as subgroups of sources, training methods, input parameters, and images need to be taken into account.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Therefore, the impact of these 4 aspects on the specificity of DL prediction models needs to be further investigated. In DL model networks, Komolafe et al [ 53 ] found a difference between ResNet and other network models in detecting COVID-19, whereas our study found no significant difference in sensitivity or specificity between ResNet and other network architectures in diagnosing and predicting the severity of COVID-19 ( Table 2 ). This result suggests that, unlike in disease detection, changing the network architecture alone may have little significant impact on DL performance and that factors such as subgroups of sources, training methods, input parameters, and images need to be taken into account.…”
Section: Discussioncontrasting
confidence: 76%
“…After evaluating sensitivity, specificity, and LR together [ 53 ], we found that DL achieved higher sensitivity and specificity in assessing the severity of COVID-19 compared to using CT [ 54 ] or neutrophil-lymphocyte ratio (NLR) alone [ 55 ]. However, DL models for longitudinal prediction of disease severity failed to exclude and confirm patients.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of 70 PROSPERO protocols was conducted as part of this systematic review, with five being centered on COVID-19. Three studies demonstrated the effectiveness of AI algorithms in tasks such as COVID-19 detection from highresolution CT images [22], patient triaging based on medical imaging [23], and conducting systematic reviews [24]. However, these studies also highlighted considerable limitations related to data heterogeneity and the limited quantity of available data for AI training, indicating a requirement for enhanced future research [23].…”
Section: Covid-19mentioning
confidence: 99%
“…Besides diagnosis ML-based applications involve early disease prediction, treatment, outcome prediction and prognosis evaluation, [13] personalized medicine, behaviour variation, drug discovery, manufacturing, clinical trial research, radiology and radiotherapy, smart electronic health records, and epidemic outbreak prediction [14]. In the light of the novel Sars-COV-2 pandemic, AI was successfully used for infection disease surveillance [15].…”
Section: In the Medical Fieldmentioning
confidence: 99%